Applied e-learning and e-teaching in higher education - Donnelly, Roisin; McSweeney, Fiona (Gale virtual reference library, 2009)
Presents international practices in the development and use of applied e-learning and e-teaching in the classroom in order to enhance student experience, add value to teaching practices, and illuminate best practices in the area of e-assessment. Provides insight into e-learning and e-teaching practices while exploring the roles of academic staff in adoption and application.